2017
DOI: 10.1002/acn3.436
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adiponectin activity in the pathogenesis of Alzheimer's disease

Abstract: A recent study suggested that insulin resistance may play a central role in the pathogenesis of Alzheimer's disease (AD). In this regard, it is of note that upregulation of plasma adiponectin (APN), a benign adipokine that sensitizes the insulin receptor signaling pathway and suppresses inflammation, has recently been associated with the severities of amyloid deposits and cognitive deficits in the elderly, suggesting that APN may enhance the risk of AD. These results are unanticipated because AD has been linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 74 publications
3
43
0
Order By: Relevance
“…Adiponectin enhances AMPK activity via AdipoR1, and, in turn, AMPK activation represses amyloidogenesis, decreases mTOR signalling, and enhances autophagy and lysosomal degradation of beta-amyloid [28]. GSK-3β is recognised as another signalling molecule in adiponectin receptor signalling pathway [14]. It should be highlighted that GSK-β is involved in tau and beta-amyloid production [29], and it is regarded as a critical molecular link between two histopathological hallmarks of AD: senile plaques and neurofibrillary tangles [30].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin enhances AMPK activity via AdipoR1, and, in turn, AMPK activation represses amyloidogenesis, decreases mTOR signalling, and enhances autophagy and lysosomal degradation of beta-amyloid [28]. GSK-3β is recognised as another signalling molecule in adiponectin receptor signalling pathway [14]. It should be highlighted that GSK-β is involved in tau and beta-amyloid production [29], and it is regarded as a critical molecular link between two histopathological hallmarks of AD: senile plaques and neurofibrillary tangles [30].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2018) found that in the ICV-STZ rat model experiment, APN supplements inhibit hyperphosphorylation of tau protein at multiple AD-related sites, improve cognitive deficits, and have neuroprotective effects. But intriguingly, it is also reported that adaptation of APN to IR may play a dual role in the formation of two markers of AD: Aβ plaques and NFTs, and perhaps its fluctuation acts as a driving force in the disease pathogenesis (Sekiyama et al, 2014;Waragai et al, 2016Waragai et al, , 2017. Therefore, according to this unique biological mechanism of APN in AD, a selective therapeutic strategy that is distinct from previous concepts may be required.…”
Section: Inhibiting Hyperphosphorylation Of Tau In Nftsmentioning
confidence: 99%
“…In this regard, evolutionary biology might provide an effective viewpoint. We previously discussed that hyperadiponectinemia in AD might be a compensatory feedback to the decreased activity of insulin/IGF-1 receptor signaling pathway during the neurodegenerative conditions (1). As the disease progresses, APN might be increased and sequestered by tau, leading to neurotoxic protein aggregation in the brain of AD (1,8).…”
Section: Mechanism Of the Apn Paradox In Admentioning
confidence: 99%
“…We previously discussed that hyperadiponectinemia in AD might be a compensatory feedback to the decreased activity of insulin/IGF-1 receptor signaling pathway during the neurodegenerative conditions (1). As the disease progresses, APN might be increased and sequestered by tau, leading to neurotoxic protein aggregation in the brain of AD (1,8). An alternative and non-exclusive possibility is that misfolding of APN might downregulate the insulin/APN signal transduction network, resulting in the decrease of neurotrophic and neuroprotective activities.…”
Section: Mechanism Of the Apn Paradox In Admentioning
confidence: 99%
See 1 more Smart Citation